Fibronectin in children with diabetes mellitus. Issue 10 (October 1984) - Muhar, U; Graninger, W; Schober, E; Schuster, E
Abstract : Fibronectin plasma concentrations were determined in 28 children with type I diabetes mellitus and 22 healthy children. No statistically significant difference was observed between the fibronectin concentrations in diabetic and non-diabetic children. Even in children with poor glycaemic control the fibronectin concentrations (glycosylated haemoglobin greater than 10%) were not significantly higher.